1977
DOI: 10.1097/00000658-197712000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Chemotaxis in Patients with Burns

Abstract: In a group of 22 patients with second and third degree burns, seven were found to have impaired chemotaxis. The chemotactic defect was present from two to 68 days and eventually became normal. The impairment was found to be due to a primary transient defect in polymorphonuclear leukocytes and not to an inhibitor or inactivator in the serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Furthermore, this impairment in chemotaxis may precede the septic episode (4) and is a transient defect in patients who survive (4,11). In contrast to the previously cited chemotactic studies, which used either neutrophils (11,14) or peripheral blood monocytes (4), the present study utilized alveolar macrophages, which also demonstrated a profound chemotactic defect (Table 3). This defect lasted at (n = 10) a Pulmonary alveolar macrophages were harvested by pulmonary lavage 4 h after a 10-s, 90°C, 26 to 28% body surface area scald burn.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, this impairment in chemotaxis may precede the septic episode (4) and is a transient defect in patients who survive (4,11). In contrast to the previously cited chemotactic studies, which used either neutrophils (11,14) or peripheral blood monocytes (4), the present study utilized alveolar macrophages, which also demonstrated a profound chemotactic defect (Table 3). This defect lasted at (n = 10) a Pulmonary alveolar macrophages were harvested by pulmonary lavage 4 h after a 10-s, 90°C, 26 to 28% body surface area scald burn.…”
Section: Resultsmentioning
confidence: 94%
“…Numerous studies of impaired leukocyte chemotaxis have been described after thermal injury (11,14). Indeed, it has been reported that the depression of in vitro chemotaxis correlates with the burn surface area and even with patient survival (4,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies (7–13) reported that bacterial phagocytosis and killing were altered after major burns, nonburn trauma, and certain surgical procedures. Chemotaxis of both neutrophils and monocytes were also depressed in burn and nonburn trauma patients (14–19). In addition, a reduction in PMN mediated oxygen‐dependent bacterial killing after major injury has been reported by several laboratories (20–22).…”
Section: Alterations In the Innate Immune Responsementioning
confidence: 99%
“…Facteurs susceptibles d'entraîner une moindre résistance du patient à l'aggression mycotique: les déséquilibres métaboliques avec acidose [23]; l'utilisation de certaines drogues: antibiotiques, corticostéroïdes; le stress [24]; diverses altérations de l'immuni té [3,13] parmi lesquelles on retiendra no tamment une diminution du chémotactisme des leucocytes [1,14]. La sollicitation exces sive du système immunologique, surtout par des germes gram négatifs, paraît souvent jouer un rôle prépondérant: des hémocultu res positives pour Pseudomonas sont fré quemment retrouvées avant que ne survien ne la surinfection mycotique [18,21], Stone et al [25], dans une étude de 18 cas de surin fection de brûlures graves par Aspergillus survenus en 15 ans, retrouvent une septicé mie par Pseudomonas dans 16 cas sur 18.…”
Section: Fadeurs Favorisantsunclassified